Effects of Chronic Stress on the Nervous System - Mannonovna, Rahimova Madina; qizi, Erkaboyeva Mohichehra Rustam (American Journal of Biology and Natural Sciences, 2025)
Chronic stress represents a persistent activation of adaptive physiological mechanisms that gradually exert detrimental effects on the nervous system. Prolonged exposure to stressors leads to sustained neuroendocrine stimulation, excessive release of stress mediators, and structural as well as functional alterations in the brain. This article examines the influence of chronic stress on central and peripheral nervous system activity, with special attention to neuroplasticity, neurotransmitter balance, neuronal survival, and cognitive-emotional regulation. The role of glucocorticoids, excitatory neurotransmitters, and inflammatory mediators in stress-induced neural dysfunction is analyzed. Understanding these mechanisms is essential for explaining the development of anxiety disorders, depression, cognitive impairment, and neurodegenerative processes associated with long-term stress. Persistent exposure to stressors initiates long-lasting biological reactions that progressively alter neural regulation and brain integrity. Continuous activation of stress-related pathways modifies neuronal signaling, synaptic remodeling, and cellular metabolism within central and peripheral neural structures. These alterations initially support adaptation but gradually shift toward dysfunction, increasing vulnerability to emotional instability, cognitive decline, and behavioral disturbances. This section summarizes how prolonged stress reshapes neural activity and contributes to the development of stress-associated neurological and psychological conditions.